Progressive pseudorheumotoid dysplasia: A presentation of four cases with slow and rapid progression and effects of early rehabilitation program - ELÇİOĞLU, HURİYE NURSEL; YAĞCI, İLKER (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2019)
Progressive pseudorheumotoid dysplasia (PPD) is a rare hereditary musculoskeletal disorder which is usually misdiagnosed due to its clinical resemblance to juvenile idiopathic arthritis. It has a high incidence in the Middle East, Gulf States, and countries of Mediterranean basin. Herein, we present four cases of PPD from Turkey (two siblings pair from the same kindred who are far paternal cousins) showing different disease courses. The progression of disease was particularly aggressive in the male sibling who suffered from severe scoliosis with more crippling joint disease. These four cases of PPD support the clinical heterogeneity and variable expressivity of PPD. In this article, we draw attention to the effects of patient education and early rehabilitation which helped to slow progression of range of motion loss.
Keywords: Juvenile idiopathic arthritis; progressive arthropathy; progressive pseudorheumatoid dysplasia; WISP3 MUTATIONS; TARDA; DIAGNOSIS; ARTHROPATHY; DISORDER; PATIENT